2015
DOI: 10.5603/fmc.2015.0004
|View full text |Cite
|
Sign up to set email alerts
|

ARCHITECT STAT High Sensitive Troponin I Familiarization Study (FAM) in the Department of Laboratory Medicine, Collegium Medicum, Nicolaus Copernicus University in Bydgoszcz, Poland

Abstract: Background. International guidelines recommend the use of cardiac troponin assays for early detection of acute myocardial infarction. New high-sensitivity assays along with improved precision and sensitivity, are now widely available, accelerating patient's diagnosis, treatment and invasive therapy. In this study we evaluated analytical performance of the Abbott ARCHITECT STAT high-sensitive troponin-I immunoassay and its 99 th percentile upper reference limit.Methods. We performed the analytical evaluation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…A more satisfactory definition of differences in cTnI circulating levels according to gender and age is now available thanks to the highly sensitive method using the ARCHITECT platform, able to measure biomarker values above the LoD value in the majority of healthy subjects from the day of birth to senescence [14,15,33,34,[49][50][51]. No studies found significant gender-related differences in cTnI values of pediatric age subjects (Table 2 and Figure 2) [15,33,34,50].…”
Section: Gendermentioning
confidence: 99%
“…A more satisfactory definition of differences in cTnI circulating levels according to gender and age is now available thanks to the highly sensitive method using the ARCHITECT platform, able to measure biomarker values above the LoD value in the majority of healthy subjects from the day of birth to senescence [14,15,33,34,[49][50][51]. No studies found significant gender-related differences in cTnI values of pediatric age subjects (Table 2 and Figure 2) [15,33,34,50].…”
Section: Gendermentioning
confidence: 99%